2012
DOI: 10.1590/s1414-462x2012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Salud mental en atención primaria en Chile: aprendizajes para Latinoamérica

Abstract: Cad. Saúde Colet., 2012, Rio de Janeiro, 20 (4): 440-7 440 Artículo OriginalResumen El presente artículo describió la experiencia chilena de los últimos 20 años con la integración de salud mental en atención primaria de salud y analizó los resultados de algunas evaluaciones, con el fin de contribuir a los procesos de aprendizaje de cómo disminuir brechas de atención. El retorno a la democracia después de la Dictadura Militar y la Declaración de Caracas fueron factores contribuyentes, así como el alto desarroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 12 publications
0
11
0
16
Order By: Relevance
“…The outcomes reported by these studies showed positive results regarding the effects that SFBT has on older adults presenting psychosocial problems and couples aiming to improve marital satisfaction. The study by Schade and colleagues (2011) on the effects of brief intervention in primary care that reduces mental health symptomology may be particularly important for Latin America because important mental conditions such as depression and anxiety are addressed at this level of health services (Alarcón, 2003;Minoletti, Rojas, & Horvitz-Lennon, 2012). Moreover, these conditions can be efficiently and effectively prevented and treated in primary care through brief interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes reported by these studies showed positive results regarding the effects that SFBT has on older adults presenting psychosocial problems and couples aiming to improve marital satisfaction. The study by Schade and colleagues (2011) on the effects of brief intervention in primary care that reduces mental health symptomology may be particularly important for Latin America because important mental conditions such as depression and anxiety are addressed at this level of health services (Alarcón, 2003;Minoletti, Rojas, & Horvitz-Lennon, 2012). Moreover, these conditions can be efficiently and effectively prevented and treated in primary care through brief interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Estes achados encontram ressonância em outros estudos que focalizam transtornos mentais graves (Minoletti, Rojas, & Horvitz-Lennon, 2012;Prates, Garcia, & Moreno 2013). Ou seja, a continuidade do contato é fundamental para a operacionalização do processo de trabalho, assim como para a efetividade das intervenções.…”
Section: Descentralização E Apoio Sistemático Longitudinalunclassified
“…También se ha buscado enfocar en la atención primaria de salud (APS). De las prioridades definidas en el plan, sólo cuatro condiciones de salud -depresión, esquizofrenia, abuso/dependencia de alcohol y drogas, y trastorno bipolar-fueron incluidos en el sistema de garantías explícitas de salud (GES) desde el 2005 4 . Actualmente, el Ministerio de Salud está elaborando un nuevo plan de salud mental para los años 2016-2025, y una ley de salud mental, cuyos lineamientos principales aún no han sido dados a conocer.…”
Section: Marco Legislativo Y Políticounclassified